Research advances in Ecuador on use of entomopathogenic fungi for control of the cattle tick, Rhipicephalus microplus: the case of Beauveria bassiana sensu lato strain INIAP L3B3 - Hidalgo, David; Ramírez, José Luis; Navarrete, Mercedes; Cevallos, Víctor; Ramos, Mario; Bravo, Bill; Carranza, Klever; Montes, Víctor; Pérez de León, Adalberto Á. (Frontiers in Fungal Biology, 2025)
Ecuador is one of the countries in the world where ticks and tick-borne diseases are major constraints on cattle health and productivity. The intense use of synthetic acaricides to manage tick infestations resulted in widespread acaricide resistance in the tick Rhipicephalus microplus, which is known to infest over 75% of the farms where cattle are raised in the country. Sustainable and environmentally friendly alternatives to control the cattle tick R. microplus are needed urgently. This minireview describes a project at the Santo Domingo Experimental Station of the National Institute of Agricultural Research to develop biopesticides for tick management to exemplify advances in collaborative research on the use of entomopathogenic fungi as active ingredients, or mycopesticides, in formulations to control R. microplus. Research and development conducted in multiple phases revealed the in vitro and in vivo acaricidal properties of B. bassiana sensu lato (s.l.) strain INIAP L3B3. These efforts followed efficacy and safety norms issued by the government agency of Ecuador in charge of controls and regulations to protect an improve animal health, plant health, and food safety. Results described herein indicate that B. bassiana s.l. INIAP L3B3 can be registered as an eco-friendly mycopesticide alternative to synthetic chemical acaricides or could complement conventional chemical acaricide applications for integrated R. microplus management programs in support of sustainable cattle raising in Ecuador.